Trust Mediates the Effect of Perceived Benefits and Perceived Convenience on the Interest in Reusing Electronic Money - Putri Rahmawati; Muhadjir Anwar (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to investigate the influence that perceived utility and perceived simplicity of use have on a person's desire to reuse electronic money, with trust serving as a moderating variable. This research is a quantitative study that was carried out utilizing a sample of individuals who reside in the city of Surabaya, have used electronic money during the last six months, and are at least 18 years old. PLS analysis, also known as partial least squares analysis, was used in conjunction with validity tests, discriminant tests, reliability tests, inner model tests, and hypothesis testing in the process of data analysis. According to the findings of this research, the perceived usefulness variable is able to encourage interest in reusing electronic money, the perceived ease of use variable is able to encourage interest in reusing electronic money, the trust variable is unable to mediate the relationship between perceived usefulness and interest in reusing electronic money, and the trust variable is able to mediate the relationship between perceived ease of use and interest in reusing electronic money; however, the perceived usefulness variable is unable to mediate the relationship.